Building the e-commerce supply chain of the future: What influences consumer acceptance of alternative places of delivery on the last-mile - Björn Asdecker (Logistics, 2021)
Background: To cope with the expected further growth in e-commerce and to be able to continue delivering at low costs, new concepts for the last-mile are needed. This paper reviews the literature and qualitatively investigates which factors influence the acceptance of four alternative place-of-delivery innovations in a business-to-consumer (B2C) context: (1) parcel lockers, (2) reception boxes, (3) trunk delivery, and (4) home access systems; Methods: The available literature was reviewed. Furthermore, 37 interviews were conducted and analyzed using the deductive category development method. In the following, abductive reasoning can derive detailed research models that may form the basis for future confirmative studies; Results: The research gains more detailed insights into how consumers perceive innovative last-mile place-of-delivery concepts. The study provides a clearer picture of what factors influence the intention to use such alternative services; Conclusions: The results can be used by logistics service providers and e-tailers through targeted communication efforts and lay the groundwork for further confirmatory research.
Keywords: 650; customer acceptance; e-commerce; home-access systems; last-mile; parcel lockers; place of delivery; reception boxes; trunk delivery